2017
DOI: 10.1080/09639284.2017.1327360
|View full text |Cite
|
Sign up to set email alerts
|

Learning groups: the effects of group diversity on the quality of group reflection

Abstract: This study explores the quality of reflection, and how group diversity affects group reflection by final-year accounting and finance undergraduates using Mezirow's [(1991). Transformative dimensions of adult learning. San Francisco, CA: Jossey-Bass] reflection model. Group work and reflective writing are now common assessment features in UK higher education. They affect students' perception of their learning experience ([Ledwith, S., & Seymour, D. (2001). Home and away: Preparing students for multicultural man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(99 reference statements)
3
2
0
Order By: Relevance
“…This is shown in the transfer tasks which test the ability of students to extend what has been learned in one context to other contexts (Sithole, 2016). Our results are consistent with prior research attesting to the benefits of teamwork (Adelopo et al, 2017;Lambert et al, 2013).…”
Section: Collaborative Learning and Application Of Knowledgesupporting
confidence: 89%
“…This is shown in the transfer tasks which test the ability of students to extend what has been learned in one context to other contexts (Sithole, 2016). Our results are consistent with prior research attesting to the benefits of teamwork (Adelopo et al, 2017;Lambert et al, 2013).…”
Section: Collaborative Learning and Application Of Knowledgesupporting
confidence: 89%
“…According to our qualitative research, many factors influence learning. Firstly, the study confirmed the findings of earlier research that heterogeneous groups have a positive impact on learning [34], [15], [35]. The groups were heterogeneous in many respects (gender, age, personality type, educational background, work experience and current employer or place of study).…”
Section: Factors Affecting Networked Cooperative Learningsupporting
confidence: 87%
“…Our study confirms the existence of these key elements in cooperative learning in a network environment. The latter two themes link our findings to the earlier research on the other factors of cooperative learning [34], [26], [15], [35]. These findings enhance our understanding of the key factors in cooperative learning in a network environment.…”
Section: Cross-organizational Team and Networksupporting
confidence: 82%
See 2 more Smart Citations